The Model Of Quality Management In Strengthening Islamic Higher Education - Azhar, Imam (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2023)
One path of continous improvement in education is by implementing total quality management, which can provide any educational institution with 3 set of practical tools for meeting and exceeding present and future customers needs, wants and expectation. This article is aimed to explore the modern concept about an education which is regarded as service industry. As service industry, educational institution should pay any attention and focus on customers’ needs, wants and expectations that is students themselves and their prospective jobs. In relevant with this, there should be specific model of management which can be implemented continuously, that is Toral Quality Management (TQM). This article is written is based on the library research. The finding shows as follows:, firstly, the implementation concept of TQM in higher education will be successful if it is supported by quality leadership; secondly, teamworks; thirdly, involving and empowering the employees at all levels of institution, such as; decision making and problem solving; fortly, there must be a strategic planning as the engine of quality improvement to guide the running of institution in realizing the customers satisfaction; lastly, there must be good and visoned management as the main factor of quality improvement process and forming an effective team work for quality.